Impact of board diversity on firm performance: Evidence from listed material companies in sri lanka - Dedunu, H.H.; Anuradha, P.A.N.S. (University of Jaffna, 2020)
The study aims to investigate the impact of board diversity on firm performance through board meetings based on listed material companies listed at the Colombo Stock Exchange in Sri Lanka. Diversity of the director board is measured through bio-demographic diversity and job related diversity. The bio-demographic diversity of the director board measured by gender, age and race, and job-related diversity measured on functional, education and organizational tenure—firm performance measured through Tobin Q and Return on Sales. The number of board meetings conducted per year was taken as a mediating variable. Listed material companies at Colombo Stock Exchange from 1985 to 2019 were the population from which twenty-eight firms that have been operating from 2013 to 2017 were filtered as the sample. Annual reports, published financial documents collected required data, and on which gender index, age index, race index, functional index, education index and organization tenure index were calculated separately. Multiple regression analysis was used to measure the direct and indirect impact of board diversities on firm performance. The light of the regression indicated a significant positive impact of gender diversity on firm performance; however, age and race diversities had an insignificant impact. Further, the impacts of functional, education and organizational tenure diversities to firm performance were negative. Finally, the study found a significant indirect impact of bio-demographic and job-related diversities to firm performance through board meetings confirming the mediating effect of the board meeting. Accordingly, policymakers and authorizes listed material firms should identify the escalating trend of women participation, educational improvement in the director board and ought to take necessary actions to maintain appropriate diversity levels in terms of bio demographic and job-related to enhance the firm performance.
Keywords: Bio demographic diversity; Board meeting; Firm performance and job-related diversity